Loss of insight in frontotemporal dementia, corticobasal degeneration and progressive supranuclear palsy - GARAVAN, HUGH PATRICK (Oxford University Press, 2007)
Loss of insight is one of the core features of frontal/behavioural variant frontotemporal dementia (FTD). FTD shares many clinical and pathological features with corticobasal degeneration (CBD) and progressive supranuclear palsy (PSP). The aim of this study was to investigate awareness of cognitive deficits in FTD, CBD and PSP using a multidimensional approach to assessment, which examines metacognitive knowledge of the disorders, online monitoring of errors (emergent awareness) and ability to accurately predict performance on future tasks (anticipatory awareness). Thirty-five patients (14 FTD, 11 CBD and 10 PSP) and 20 controls were recruited. Results indicated that loss of insight was a feature of each of the three patient groups. FTD patients were most impaired on online monitoring of errors compared to the other two patient groups. Linear regression analysis demonstrated that different patterns of neuropsychological performance and behavioural rating scores predicted insight deficits across the three putative awareness categories. Furthermore, higher levels of depression were associated with poor anticipatory awareness, reduced empathy was related to impaired metacognitive awareness and impaired recognition of emotional expression in faces was associated with both metacognitive and anticipatory awareness deficits. The results are discussed in terms of neurocognitive models of awareness and different patterns of neurobiological decline in the separate patient groups.
PUBLISHED
Keywords: loss of insight; frontotemporal dementia; progressive supranuclear palsy; corticobasal degeneration; neuropsychological deficits